Evaluation of first-year university students’ engagement to enhance student development / Yenwan Chong and Hooi Sin Soo - Chong, Yenwan; Soo, Hooi Sin (Universiti Teknologi MARA, 2021)
The COVID-19 crisis has dramatically impacted university education as well as created new challenges for tertiary learning institutions. The pandemic has exacerbated graduate unemployment and increased student dropout rates. In response to these unprecedented challenges, universities are formulating more student development initiatives to support new students to transition into university and produce holistic graduates with essential soft skills. Student engagement evaluation can help inform and enhance the implementation of student development programs. In this study, seven domains of first year university students’ engagement were evaluated namely Academic Engagement (AE), Beyond-class Engagement (BE), Intellectual Engagement (IE), Online Engagement (OE), Peer Engagement (PE), Student-staff Engagement (SE) and Transition Engagement (TE). This study found that university freshmen’s Online Engagement (OE) was the strongest while their Academic Engagement (AE) was the weakest. This study also discovered that first year university students’ engagement were weakest with regard to reading of textbooks before attending class, asking questions in class and borrowing books from the university library. Future student development programs targeted at first year university students could be enhanced by increasing the use of ICT in teaching and learning as well as increasing efforts in assisting new students to transition from school to university learning environments by inculcating good reading habits and encouraging active class participation.